Double Emulsion Microencapsulation System for Lactobacillus rhamnosus GG Using Pea Protein and Cellulose Nanocrystals - Sanket Prakash Vanare; Rakesh K. Singh; Jinru Chen; Fanbin Kong (Foods)
Microencapsulation using a double emulsion system can improve the viability of probiotic cells during storage and digestion. In this study, a double emulsion system WC/O/WF was designed to microencapsulate Lactobacillus rhamnosus GG using pea protein (PP) and cellulose nanocrystals (CNCs) at various proportions, and the effect of their proportions on the stability and efficacy of the encapsulation system was studied. The double emulsions were prepared by a two-step emulsification process: the internal aqueous phase containing probiotic strain (WC) was homogenized into the oil phase (O), which was then homogenized into the external aqueous phase (WF) containing 15% wall materials with varying proportions of PP and CNCs [F1 (100:0), F2 (96:4), F3 (92:8), F4 (88:12), F5 (84:16), F6 (80:20)]. The incorporation of CNCs significantly lowered the average particle size and improved the stability of the emulsions. The encapsulation efficiency did not differ significantly across the tested formulations (63–68%). To check the effectiveness of the designed system, a simulated digestion study was conducted in two phases: gastric phase and intestinal phase. The double emulsion microencapsulation significantly improved the viability of encapsulated cells during digestion compared against free cells. Microscopic analysis along with assessment of protein hydrolysis of the double emulsions during the simulated digestion demonstrated a two-stage protection mechanism. This study presented promising results for employing a double emulsion system for the microencapsulation of probiotics and the potential of PP and CNCs in designing such systems.